중국 고등 간호전문대학생의 직업정체성이 학습만족도에 미치는 영향 : 자기효능감 매개효과를 중심으로 - 왕학미; 문숙자 (다문화건강학회지, 2024)
Purpose: The purpose of this study is to understand the effect of job identity of Chinese high school nursing college students on learning satisfaction, focusing on the mediating effect of self-efficacy. Method: The subjects of this study were 2nd and 3rd graders of the Department of Nursing at T Vocational School in China, and the data collection period is from September 1st to October 30th, 2023, and the collected data was processed using SPSS Windows 24.0 Program. Results: According to the general characteristics of the subjects, there were statistically significant differences in job iden- tity (t=2.163, p=.031) according to gender, job identity (t=1.998, p=.046) and learning satisfaction (t=2.093, p=.037) ac- cording to grade. In addition, there was a positive correlation between job identity, self-efficacy, and learning satisfaction, and self-efficacy was found to play a partial mediating role in the relationship between job identity and learning sat- isfaction of high school nursing college students. Conclusion: Based on the results of the study, schools and educators need a broad interest in job identity so that students can give meaning to their roles and establish beliefs or values to improve their self-efficacy and learning satisfaction. KCI Citation Count: 0